Pattern of major injuries after motorcycle accidents in Egypt: The Mansoura Emergency Hospital experience. (January 2017) - Fouda, El Yamani; Youssef, Mohamed; Emile, Sameh H; Elfeki, Hossam; Thabet, Waleed; Abdallah, Emad; Elshobaky, Ayman; Toma, Mohamed S; Khafagy, Wael
Background and aim: Motorcycle accidents are one of the leading causes of road traffic injuries and mortality. The aim of this study was to determine the common patterns of major injuries associated with motorcycle accidents in patients attending Mansoura University Emergency Hospital in Egypt, and to measure the magnitude of the problem in our community. Patients and methods: Patients involved in motorcycle crashes who were admitted to the hospital during August 2014 to April 2015 were retrospectively reviewed. All age groups and both genders were included. Results: Two hundred patients (181 males) with a mean age of 30.7 ± 10.5 years were included with the majority of patients aged 20–40 years. Head injuries were the most frequent fatal injuries (9/61) patients; orthopedic injuries were the most common injuries, occurring in 78.5% of victims. Multisystem injuries occurred in 28% of patients. None of the motorcyclists involved in accidents wore helmets. Conclusion: Motorcycle accidents are a common cause of road traffic injuries and mortalities in Egypt, occurring mainly in males aged 20–40 years. The majority of victims had an isolated trauma to single body system. Orthopedic injuries were the most common and least fatal type of injuries. The highest fatalities were among patients with chest injuries then patients with head injuries. None of the victims wore protective clothing or helmets at the time of accident.